Immunomodulatory Effect of Chinese Herbal Medicine Formula Sheng-Fei-Yu-Chuan-Tang in Lipopolysaccharide-Induced Acute Lung Injury Mice. (13th August 2013) - Lin, Chia-Hung; Yeh, Ching-Hua; Lin, Li-Jen; Wang, Shulhn-Der; Wang, Jen-Shu; Kao, Shung-Te
Abstract : Traditional Chinese medicine formula Sheng-Fei-Yu-Chuan-Tang (SFYCT), consisting of 13 medicinal plants, was used to treat patients with lung diseases. This study investigated the immunoregulatory effect of SFYCT on intratracheal lipopolysaccharides- (LPS-) challenged acute lung injury (ALI) mice. SFYCT attenuated pulmonary edema, macrophages, and neutrophils infiltration in the airways. SFYCT decreased inflammatory cytokines, including tumor necrosis factor- α (TNF α ), interleukin-1 β, and interleukin-6 and inhibited nitric oxide (NO) production but increased anti-inflammatory cytokines, interleukin-4, and interleukin-10, in the bronchoalveolar lavage fluid of LPS-challenged mice. TNF α and monocyte chemotactic protein-1 mRNA expression in the lung of LPS-challenged mice as well as LPS-stimulated lung epithelial cell and macrophage were decreased by SFYCT treatment. SFYCT treatment also decreased the inducible nitric oxide synthase expression and phosphorylation of nuclear factor- κ B (NF- κ B) in the lung of mice and macrophage with LPS stimulation. SFYCT treatment dose dependently decreased the LPS-induced NO and reactive oxygen species generation in LPS-stimulated macrophage. In conclusion, SFYCT attenuated lung inflammation during LPS-induced ALI through decreasing inflammatory cytokines production while increasing anti-inflammatory cytokines production. The immunoregulatory effect of SFYCT is related to inhibiting NF- κ B phosphorylation.